Gaya Kepemimpinan dalam Mereduksi Tingkat Stress Karyawan di Perusahaan - Ageng Saepudin Kanda; Wendy Irsyadul Arkan (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted to examine the influence between leadership styles on employee work stress levels in several companies. The research method used is a literature review of several previous studies. Used 5 relevant literature that will be reviewed both nationally and internationally with a range of years 2019-2023. The analysis technique used is descriptive analysis. The results found that Tokopedia employees felt that the leadership style applied was in accordance with what they expected. They consider that the leader has applied the right style in every work-related condition. The stress level of employees at Tokopedia is relatively low. The analysis that has been done shows a negative significant relationship between leadership style and job stress levels. Employees who feel in accordance with the leadership style of their superiors will have lower stress levels. The results of this study can be a reference for related companies to study other factors that cause job stress.